Calculation of greenhouse gas emissions for a carbon recycling system using mineral carbon capture and utilization technology in the cement industry. (20th August 2021) - Izumi, Yoshito; Iizuka, Atsushi; Ho, Hsing-Jung
Abstract: Cement is widely produced and used. Cement production consumes a significant amount of energy and natural resources, and it accounts for approximately 7% of man-made greenhouse gas (GHG) emissions in CO2 -equivalents globally. The cement industry is continually conducting research and development into energy conserving and low-carbon technologies to reduce CO2 emissions. Furthermore, the industry will be at the heart of a carbon recycling system along cement and concrete value chain using newly developed mineral carbon capture and utilization (MCC&U) technology to reduce CO2 emissions substantially during clinker and/or cement production. This paper provides fundamental calculations for the determination of CO2 emissions from the MCC&U technology in the cement industry, which will contribute to the calculation of GHG inventories and life cycle assessments of the system. Demonstration experiments were conducted to develop an accounting formula and clearly determine CO2 emissions for recarbonate utilization as a cement raw material. Highlights: A carbon recycling system using MCC&U in the cement industry substantially reduces CO2 emissions. An accounting methodology of GHG emissions from MCC&U is considered and introduced. Recarbonates react as carbon neutral when repeatedly calcinated in the cement kiln.